Measuring the organisational health of acute sector healthcare organisations: Development and validation of the Healthcare-OH survey. (2nd January 2021) - Nicolay, Chris R.; Williams, Stephen P.; Brkic, Milica; Purkayastha, Sanjay; Chaturvedi, Sankalp; Phillips, Nelson; Darzi, Ara
ABSTRACT: Healthy organisations have a strong provision of the vital elements required for long-term sustainable success and proponents of organisational health concern themselves with the recognition and measurement of these elements. However, despite many leading companies focussing on organisational health in addition to organisational performance there has been very limited work within the context of healthcare to date. This is the first study to look specifically at the measurement of organisational health within the context of acute sector healthcare organisations. The Healthcare-OH survey was developed in three sequential stages. In the first, a qualitative interview study was used to establish the elements of organisational health within acute sector healthcare organisations. The second stage involved item generation to formulate a draft questionnaire which was then piloted across a sample of healthcare staff and analysed by way of exploratory factor analysis to create the final questionnaire. The third stage comprised a final round of pilot testing with confirmatory factor analysis to confirm data model fit. We believe that the Healthcare-OH survey provides an innovative and novel way of considering the performance of healthcare organisations.